2021
DOI: 10.1096/fj.202100451r
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and bone metabolism

Abstract: Osteoporosis is the most common metabolic skeletal disease. It is characterized by the deterioration of the skeletal microarchitecture and bone loss, leading to ostealgia, and even bone fractures. Accumulating evidence has indicated that there is an inextricable relationship between the gut microbiota (GM) and bone homeostasis involving host–microbiota crosstalk. Any perturbation of the GM can play an initiating and reinforcing role in disrupting the bone remodeling balance during the development of osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 303 publications
(637 reference statements)
0
59
0
Order By: Relevance
“…Parasutterella was initially defined as a core component of the human and mouse GM that can contribute to host health in 2019 ( Ju et al., 2019 ). The key role of Parasutterella is to enhance the catabolism of tryptophan, tyrosine, and bile acid components ( Ju et al., 2019 ), which are potentially related to bone metabolism ( Lu et al., 2021 ). A recent study has identified a strain of Odoribacter that protects against colitis and colorectal cancer, and demonstrated a crucial role in inducing immunosuppressive Th17 cells ( Xing et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parasutterella was initially defined as a core component of the human and mouse GM that can contribute to host health in 2019 ( Ju et al., 2019 ). The key role of Parasutterella is to enhance the catabolism of tryptophan, tyrosine, and bile acid components ( Ju et al., 2019 ), which are potentially related to bone metabolism ( Lu et al., 2021 ). A recent study has identified a strain of Odoribacter that protects against colitis and colorectal cancer, and demonstrated a crucial role in inducing immunosuppressive Th17 cells ( Xing et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites bridge the distance between the GM and skeletal system ( Zaiss et al., 2019 ). Various GM-derived metabolites have displayed bone metabolism-related bioactivities ( Lu et al., 2021 ). Purine metabolism is one of the metabolic pathways enriched by differential metabolites after HFD ( Figure 4G ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are many studies on the relationship between intestinal flora and bone metabolism ( 6 ). The interactions of the host microbiota are key factors for health and can ultimately be used to develop a stable microbial community ( 7 ).…”
Section: Introductionmentioning
confidence: 99%